Pengaruh Gratis Ongkos Kirim, Diskon dan Online Customer Review Terhadap Keputusan Pembelian Konsumen Tiktok Shop - Frisca Della Oktavianingrum; Basar Maringan Hutahuruk (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Development of Technology Over the past few years, technology has advanced rapidly and will continue to do so indefinitely. In Indonesia today, online shopping has emerged as a trend and option for acquiring a wide range of desired goods. This study aims to determine how free delivery, limits, and online customer surveys influence purchase decisions on the Tiktokshop Commercial center. Comparative causality is used in this study. This study uses a type of quantitative data because the presented data are related to numbers or scoring. Customers who use TikTok Shop are the focus of this study. Subsequently, the plan of this study utilizes a quantitative methodology, utilizes a coincidental examining technique, and afterward utilizes a non-likelihood testing strategy to make a populace and an example. The study reveals that TikTok Shop purchase decisions are influenced simultaneously by free shipping, discounts, and online customer reviews. The connection between free transportation, limits and online client audits is at the same time sure, intending that in the event that the general factors of free delivery, limits and picture are improved, the buy choice will increment.